The Relationship between Intensity of Social Media and Learning with Learning Outcomes of Sociology in Ngawi Regency - Fikri Haykal Amien; Nurhadi Nurhadi; Septina Galih Pudyastuti (STKIP Taman Siswa Bima, 2023)
Teenagers, one of Indonesia's primary consumers, mainly access social media using smartphones. As a student, they use it freely, even when the teachers are in classes. Schools fear unlimited access to social media because the distraction could affect their scores. However, it also could bring positive change. 2019 is the year when the global pandemic crippled the world. Schools are forced to operate online with no direct supervision of the teachers. Social media could be used as an alternative teaching method in such events. This study aimed to determine the relationship between the intensity of social media use and learning related to learning outcomes. The use of social media carried out by students regardless of time affects student learning outcomes, both positively and negatively. Teachers use social media to support the value obtained by students to the maximum through utilization in learning. This study uses correlational quantitative methods with problem characteristics in the form of relationships between 2 or more correlations. The data collection techniques used were questionnaires and interviews. The analysis techniques used are normality test, linearity test, double linear regression test, and Pearson correlation test. The results obtained are: (1) a positive and significant relationship exists between the intensity of social media use and student sociology learning outcomes. (2) there is a positive and significant relationship between learning and student sociology learning outcomes. (3) there is a positive and significant relationship between the intensity of social media and learning with the sociology learning outcomes of grade XI social studies students of SMA N 1 Ngawi. The use of social media can be beneficial for students in learning and learning outcomes of student sociology